Elucidating mechanisms of action of environmental contaminants from Doce River in Brazilian fish embryos using metabolomics and chemometric methods - Yamamoto, Flávia Y. [UNESP]; Batista, Larissa A.; Santos, Mayara P.; Bedia, Carmen; Lacorte, Silvia; Cavalcante, Rivelino M.; Grassi, Marco T.; de Souza Abessa, Denis M. [UNESP]; Tauler, Romà (Elsevier, 2025)
Mining and other essential economic activities have a long historical contamination impact on diverse aquatic environments, such as the Doce River Basin (DRB), in Southeast Brazil. High concentrations of metals combined with organic chemicals released from multiple sources of contaminants may trigger complex toxicity pathways that are complicated to interpret and distinguish. This study aimed to investigate mechanisms of toxicity of environmental chemicals from DRB using a comprehensive untargeted LC-HRMS metabolomics approach (data-independent acquisition of all ion-fragmentation mode), in fish embryos (Rhamdia quelen) exposed to complex chemical mixtures. The Regions of Interest (ROI) Multivariate Curve Resolution (MCR) approach was applied to compress and resolve data-independent acquisition (DIA) LC-MS/MS complex datasets mode. Fish embryos exposed for 96 h to 6 treatment sample groups showed a distinct pattern of responses when compared to controls, with downregulated essential metabolites, such as amino acids, as a main response, especially for metal exposure. Organic contaminants extracted from sediments combined with inorganic elements have shown non-additive effects, with inorganics possibly exerting greater influence on metabolic responses. The results helped to investigate and distinguish the effects of different complex mixtures of environmental chemicals on fish embryo samples. ROIMCR approach is shown to be a suitable strategy for the analysis of large metabolomics-derived data in the investigation of the effects of different classes of environmental chemicals on aquatic biota and ecosystems.
Keywords: Environmental complex mixtures; Metabolome; ROIMCR chemometrics approach